A checklist of free-living marine Nematodes along Sarawak Coastal waters - Mohd Rosli, Norliana; Shabdin, M.L.; Cheng, Ann Chen (Universiti Malaysia Sarawak (UNIMAS), 2010)
The exploration and studies on marine meiofauna such as nematodes are still at its infancy stage in Sarawak. Few detailed studies had been conducted on marine nematodes up to species level. The aim of this study is to establish a database for marine nematodes in Sarawak. This study was carried out at 15 sampling sites along the Sarawak coastal waters. A total of 93 nematode species were recorded (19 families, 38 genera and 5 suborder). Xyalidae was represented by 16 species, followed by Desmodoridae (9 species) and Cyatholaimidae (8 species). A total of 93 species of free-living marine nematodes were documented along the Sarawak coastal waters.